THE THE EXISTENCE OF THE AGRICULTURAL SECTOR IN THE ECONOMIC STRUCTURE OF CENTRAL SULAWESI PROVINCE - Adnan Putra Pratama; Garist Sekar Tanjung; Moh. Wahyudi Priyanto (AGROLAND The Agricultural Sciences Journal (e-Journal), 2023)
Central Sulawesi's agricultural sector is classified as a substantial sector. This study aims to identify the existence of the agricultural sector in the economic structure of Central Sulawesi. Data analysis used Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Shift Share Analysis methods. The data used is based from the Central Statistics Agency for Central Sulawesi and Indonesia in 2015-2020 based on constant prices. The results showed that the agricultural sector of Central Sulawesi was classified as the base sector with the highest average LQ value and was followed by the mining and quarrying sector. Meanwhile, the results of the DLQ analysis show that the agricultural sector is threatened with repositioning in the future. The combined analysis of LQ and DLQ indicates that the agricultural sector in Central Sulawesi is on a basic non-prospective. The results of shift-share analysis (Nij) show that the highest performance in the agricultural sub-sector is produced by the plantation sub-sector and the fishery sub-sector. The industrial mix value (Mij) from the agricultural sector and all sub-sectors mostly shows negative numbers, so only three agricultural sub-sectors, including the developed sector in Central Sulawesi Province include the horticulture sub-sector, livestock sub-sector, and fishery sub-sector. Based on the value (Cij) of the agricultural sector, it shows a negative number, so the sub-sectors that need to be improved include the food crops sub-sector, the horticulture sub-sector, the plantation sub-sector, and the fisheries sub-sector. It is necessary to pay attention to increasing labor wages in the agricultural sector and improving the performance of agro-industry in Central Sulawesi to create added value.